Experimental study on the liquid desiccant dehumidification performance of microencapsulated phase change materials slurry. (15th January 2022) - Dong, Honglin; Wang, Dandan; Niu, Xiaofeng; Zhang, Yue; He, Xu; Ke, Qing; Lu, Zhiheng
[Abstract]: In this study, the idea of using microencapsulated phase change materials slurry (MPCMS) as a liquid desiccant to achieve "auto internally cooled" dehumidification was verified and investigated experimentally. The results indicated that, the addition of MicroPCMs to LiCl solution significantly improved the dehumidification performance, the temperature-rise of the liquid desiccant could be effectively restrained, and the dehumidification performance of the MPCMS improved with the increase in the amount of MicroPCMs. When the mass concentration of the MicroPCMs reached 2.0%, the moisture removal rate and dehumidification effectiveness increased by 24.0% and 23.1%, respectively. The contribution ratio of the phase change endothermic effect of MicroPCMs to the dehumidification enhancement was 50–60%, the reduction of the MPCMS surface vapor pressure also played an important role. The impact of several factors on the dehumidification performance, including the mass concentration of the MicroPCMs, temperature and flow rate of the MPCMS, process air inlet state, and flow rate were analyzed. The dehumidification performance was improved most significantly when the MPCMS inlet temperature was close to the onset phase transformation temperature of the MicroPCMs. In addition, empirical correlations with mean relative deviations of 5.1% and 12.74% were proposed to predict the dehumidification effectiveness and the Sherwood number. Highlights: The effect of MicroPCMs on dehumidification performance is verified experimentally. Moisture removal rate/dehumidification efficiency of MPCMS are enhanced greatly. The temperature-rise of liquid desiccant can be restrained by the MicroPCMs. The slurry inlet temperature and the concentration of MicroPCMs are critical. Empirical correlations are proposed to predict dehumidification efficiency and Sh.